Born for Blessings: - Tay, Moses (Genesis Books, 1999)
Born for Blessings testifies to the faithfulness of God from generation to generation. It recounts the battles and victories of this doctor-turned-bishop who has greatly influenced the churches in Singapore, South East Asia and even America. Indeed, God has used this fearless man to be a blessing to many people and to do great exploits for the Lord